PROPHET MUHAMMAD'S PROPHETIC BUSINESS STRATEGY: COMPARISON WITH MANAGEMENT THEORY AND ITS IMPLICATIONS FOR CHARACTER EDUCATION - Yasin, Nur Ali; Hidayati, Arini; Nurlailin, Wiwik (UTSAHA: Journal of Entrepreneurship, 2024)
This article aims to examine the business strategy of the Prophet Muhammad SAW. from a modern management perspective and to outline its implications for strengthening character education. Through a descriptive qualitative approach based on literature studies, this study reveals that the Prophet SAW applied business principles that include honesty, trustworthiness, partnership, courage to take risks, efficiency, and servant leadership. These principles are then analyzed comparatively with modern management theories such as business governance, risk management, and transformational leadership. The results of the study show that the Prophet SAW. applied a business strategy based on noble values, such as honesty, trustworthiness, fair partnership, efficiency in resource management, courage to take wise risks, and servant leadership. These values are then studied comparatively with modern management theories such as stakeholder theory, servant leadership, value-based management, and risk management. It was found that the Prophet's business principles have strong relevance to current management practices, while also making a significant contribution to shaping the character of entrepreneurs with integrity and ethics. Therefore, the integration of prophetic business strategies into education, especially in entrepreneurship learning, is very important to build a generation that is not only economically competent but also morally and spiritually strong.